Technology for Producing Carbon Nanotubes on the Laboratory Setting for Students - P.A. Nesterenkov; A.G. Nesterenkov (Журнал нано- та електронної фізики)
This work presents results of studies of an improved method for producing carbon nanotubes using a low-amperage electric arc and the electromagnetic field of the coil connected in series with the electrodes. Micro- images of nanotubes produced by scanning and transmission electron microscopy are shown. Here we presents developed laboratory setting for laboratory works based on research results.